Kajian Struktural, Sosial, Budaya, Agama, Dan Nilai Pendidikan Dalam Novel Harimau! Harimau! Karya Mochtar Lubis - Ghufroni Ghufroni (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Muhadi Setiabudi (UMUS) Brebes., 2020)
This study aims to describe: 1) the structure of the Tiger novel! Tiger! 2) The social background of the Tiger novel! Tiger! 3) Cultural background of the Tiger novel! Tiger! 4) Religious background, and 5) Educational value in the Tiger novel! Tiger!. This study uses a qualitative descriptive method with a sociological approach to literature. Sources of research data consisted of objective data sources in the form of text data, genetic data sources in the form of author biographies and informants by conducting interviews with observers and literature lovers. Based on the results of the analysis of this study it can be concluded as follows: 1) The structure of the novel